Answer: x = 0, y = 0
Explanation:
x + y = 27y = 8x
Consider the first equation. Subtract 27y from both sides.
x + y = -27y = 0
Combine y and -27y to get -26y
x - 26x = 0
Consider the second equation. Subtract 8x from both sides.
27y - 8x = 0
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for the variable in the other equation.
x - 26y = 0, -8x + 27y = 0
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
x - 26y = 0
Add 26y to both sides of the equation.
x = 26y
Substitute 26y for x in the order equation,
-8x + 27y = 0.
-8 x 26y + 27y = 0
Multiply -8 times 26y
-208y + 27y = 0
Add -208y to 27y
-181y = 0
Divide both sides by -181.
y = 0
Substitute 0 for y in x = 26y. Because the resulting equation contains only one variable, you can solve for x directly.
x = 0